Urbanização extensiva na Amazônia Oriental: escavando a não-cidade em Carajás - Rodrigo Castriota de Mello Santos (2021)
This work is based on a double premise. On the one hand, a renewed conceptualization of urbanization is crucial to understand socioeconomic, spatial and ecological transformations in the Amazon both historically and contemporarily. Considering its concentrated and extended dimensions as well as its mediating function, urbanization allows for a reinterpretation of the various rounds of regional colonization, homogenization and socio-environmental degradation, in addition to the new materialities and radical subjectivities that emerge with the expansion of the urban-industrial universe. At the same time, the study of these same transformations in the Amazon creates an opportunity to rehabilitate the field of urban studies and to displace the “canonic” geographic imagination within Brazilian scholarship, for too long founded on the old urban-rural dichotomy, on the southeastern experience and on its privileged object of study: the city. Within this perspective, the region of Carajás, in the Eastern Amazon, is a privileged terrain of analysis due to the diversity of forms and processes of concentrated and extended urbanization that have been unfolding in past decades. Taking mining and other neo-extractive dynamics as inducers of urbanization processes, I discuss both geohistorical layers of regional socio-spatial transformations, as well as contemporary processes – particularly the transformations in the municipality of Canaã dos Carajá driven by the implantation of the S11D Mining Complex, built by Vale between 2011-2016, that shelters the largest open-pit mine of human history. Based on fieldwork data –participant observation, semi-structured interviews, photographs – and further documental, historical and cartographic materials, this work presents and discusses, on the one hand, the trajectory of a mining town and, on the other, the complexities and diversities of the “non-city” deeply transformed by urbanization. On the one hand, the boom and the decline of the urban center that houses the migrant labor force; on the other, the mining-induced extended urbanization expressed in highways, railroads, hydroelectric dams and conservation units, as well as in the reorganization of municipal agrarian space – including the formation of landless workers settlements in areas that are either controlled or intended by Vale. In these processes of appropriations and contestations, I emphasize the emerging relations between new materialities, new subjectivities and new possibilities attached to urbanization processes – from massive mining and logistics assemblies and the unfolding forms of oppression, vigilance and control, to the new forms of collective action and citizenship claims from the “non-city”. The region of Carajás enables the destabilization of the urban-rural dichotomy; the tensioning of major categories in the field of urban studies, often mobilized as self-evident terms; the reassertion of the concept (and the process) of extended urbanization; and, finally, the critique of both academic and non-academic perspectives that uncritically magnify or celebrate “the city” as a conceived, perceived or lived entity towards a critique of cityism.